2022
DOI: 10.1101/2022.02.16.480779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of the tuft cell/ILC2 axis reduces gastric tumor development in mice

Abstract: Although gastric cancer is a leading cause of cancer-related deaths, systemic treatment strategies remain scarce. Here we explore a metabolite-triggered circuit between epithelial tuft cells and innate lymphoid type 2 cells (ILC2) that is evolutionarily optimized for intestinal remodeling in response to helminth infection. We demonstrate that tuft cell-derived interleukin 25 (IL25) acts as an alarmin on ILC2s to induce the release of IL13 as a growth factor for tuft cells, and propose that this model drives ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Recent studies have shown that targeting ILC2s can have therapeutic potential in preventing gastric inflammation and cancer development, and even reversing the pathological changes associated with metaplasia after disease onset. Attempts have been made in mouse models through genetic ablation of ILCs or antibody-mediated blockade of IL-13 or IL-25, which can reduce the growth of gastric cancer [ 141 ]. More specifically, ILC2 depletion via treatment with CD90.2 antibodies has also been shown to directly protect the stomach from SPEM development [ 142 ].…”
Section: Roles Of Ilc Subsets In Gastric Oncogenesismentioning
confidence: 99%
“…Recent studies have shown that targeting ILC2s can have therapeutic potential in preventing gastric inflammation and cancer development, and even reversing the pathological changes associated with metaplasia after disease onset. Attempts have been made in mouse models through genetic ablation of ILCs or antibody-mediated blockade of IL-13 or IL-25, which can reduce the growth of gastric cancer [ 141 ]. More specifically, ILC2 depletion via treatment with CD90.2 antibodies has also been shown to directly protect the stomach from SPEM development [ 142 ].…”
Section: Roles Of Ilc Subsets In Gastric Oncogenesismentioning
confidence: 99%
“…High expression of POU2F3 was found in three neuroendocrine carcinoma of the gastrointestinal systemincluding colon, esophageal and gastric cancers (Yachida et al, 2022). Inhibition of the tuft cell-ILC2 axis by genetic ablation of tuft cells, ILC2s or antibody-mediated neutralization of IL-13 or IL-25 attenuated gastric tumor development in mice (O'Keefe et al, 2022). DCLK1expressing tuft cells are one of the two main sources of ACh within the gastric mucosa (Hayakawa et al, 2017).…”
Section: Gastric Cancermentioning
confidence: 99%
“…These results suggest that ILC2s play a facilitating role in the Hpmediated "CAG-GC chain", but the specific molecular mechanism still needs to be further studied. In mice, tuft cellderived IL-25 stimulates ILC2s to release IL-13, a growth factor for tuft cells, and this circle drives early metaplastic remodeling and gastric tumorigenesis (61). Genetic ablation of murine ILC2s, tuft cells or antibody neutralization of ILC2-derived type 2 cytokines suppresses gastric tumor growth (61).…”
Section: Gastric Carcinoma (Gc)mentioning
confidence: 99%
“…In mice, tuft cellderived IL-25 stimulates ILC2s to release IL-13, a growth factor for tuft cells, and this circle drives early metaplastic remodeling and gastric tumorigenesis (61). Genetic ablation of murine ILC2s, tuft cells or antibody neutralization of ILC2-derived type 2 cytokines suppresses gastric tumor growth (61). Singlecell RNAseq of gastric leukocytes have revealed that murine ILC2s highly express the glucocorticoid and androgen receptors; glucocorticoids and androgens synergistically inhibit the transcription of ILC2-derived IL-13, and simultaneous deficiency of glucocorticoids and androgens in mice results in the development of gastric inflammation and metaplasia (62).…”
Section: Gastric Carcinoma (Gc)mentioning
confidence: 99%